Democratization of Serbian society through the prism of property tax - Cvjetković Ivetić, Cvjetana; Milošević, Goran; Milašinović, Srđan (Sociološki pregled, 2023)
The process of fiscal decentralization, typical of contemporary societies, in addition to the fiscal effect, also has a political effect. Namely, because bearers of political power need to get closer to citizens, fiscal decentralization is often seen Milanovic as part of the democratization process in a society. Within that process, property tax is gaining more and more importance. In that respect, Serbia is no exception. The aim of the paper is to determine whether property tax in Serbia has the characteristics of an instrument for achieving fiscal decentralization. Moreover, the authors will also determine how the property tax, as a significant source of revenues for local authorities, contributes to the development of democracy in Serbian society at the local level.
Keywords: property tax; fiscal decentralization; local democracy